Pelatihan Tata Kelola Keuangan Dan Penyusunan Laporan Kegiatan Pokdarwis Desa Cokro, Kabupaten Klaten - Yuwono, Cahyo; Karsinah; Prihastari, Ema Butsi; Amidi (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Good financial governance capacity is one of the main pillars for the sustainability of community-based organizations, including Tourism Awareness Groups (Pokdarwis). Unfortunately, in many tourist villages, financial management still faces various challenges, such as limited administrative knowledge, lack of technical skills in record-keeping, and the absence of standardized reporting formats. This community service program was carried out in Cokro Village, Klaten Regency, with the aim of improving the competence of Pokdarwis Tjakrawala administrators in managing finances and preparing activity reports in a systematic, transparent, and accountable manner. The implementation method was designed in a participatory manner through a combination of material delivery, group discussions, hands-on practice (learning by doing), case simulations, local context-based financial record-keeping simulations, and practice in preparing activity reports. The participants consisted of core administrators and active members of Pokdarwis. The evaluation was conducted by comparing the results of the pre-test and post-test, as well as assessing the activity report products produced by the participants. The results showed a significant increase in the average score of participants’ understanding, from 54.2 in the pre-test to 86.5 in the post-test, or an increase of 59.6%. A total of 87% of participants successfully prepared activity reports according to standardized formats, with a high level of completeness and accuracy. In addition, participants also demonstrated increased confidence in applying new skills in their work environment. These findings indicate that hands-on training combined with relevant case studies can improve financial management skills and strengthen institutional governance.